Linguistic and Ethical Dimensions of the Qur’anic Term Mihrab as an Initial Framework for the Liberation of Bayt al-Maqdis - Lathif, Taqiyah Syamsul Arifin Abdul; Muassomah, Muassomah; Rohmah, Galuh Nur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2025)
This study examines the linguistic and ethical meanings of the Qur’anic term miḥrāb and its connection to the broader concept of liberation, particularly the liberation of Bayt al-Maqdis. The problem addressed in this research is the limited scholarly attention to miḥrāb beyond its conventional definition as a physical prayer niche, despite its deeper symbolic significance in the Qur’anic discourse. The study aims to clarify how miḥrāb functions as a spiritual, moral, and prophetic category that shapes individual and communal transformation. Using a textual and semantic analysis of four primary verses—Q 3:37, Q 3:39, Q 19:11, and Q 38:21—this research employs Ṭāhā ʿAbd al-Raḥmān’s theory of al-qirāʾah al-iʾtimāniyyah to explore the ethical trust embedded in the concept. The findings indicate that miḥrāb symbolizes a sacred space of spiritual discipline, moral refinement, and prophetic justice, serving as a formative arena for nurturing rabbānī leadership and spiritually liberated communities. Consequently, the liberation of Bayt al-Maqdis must begin with revitalizing spirituality through the symbolic and ethical dimensions of miḥrāb, rather than relying solely on militaristic approaches. The study contributes a conceptual framework that positions miḥrāb as a foundational paradigm for the civilizational liberation project within Islamic thought